Iron Age utilization of silver fir (Abies alba) wood around the Heuneburg: local origin or timber import? - Million, Sebastian; Eisenhauer, Anton; Billamboz, André; Rösch, Manfred; Krausse, Dirk; Nelle, Oliver (Quaternary international, 2018)
The larger area of and around the Early Iron Age fortress Heuneburg is focus of decades of archaeological excavations and observations. Additionally, to deciduous oak (Quercus sp.) known as the main timber during this period (Middle to Late Hallstatt c. 750-450 BCE), silver fir (Abies alba) was found recently on the Heuneburg plateau itself and its surroundings. Silver fir is now recognized being a significant source of timber during the Iron Age, in a region where its nowadays natural status is debated and its occurrence is rare. The aim of this study was to determine the possible source of the used timber, which might have been taken from the some 80 km distant Abies-rich Black Forest on the primary bed rock or from stands developed on younger geological formations nearer to the site. For this approach, radiogenic strontium isotope (87Sr/86Sr) analyses were performed on waterlogged wood and on charcoal remains buried in four archaeological contexts from Late Hallstatt period around the princely seat Heuneburg. The 87Sr/86Sr ratios were compared to those of living trees, soils and sediments with respect to the diverse geological background. The geological ground of the archaeological wood was narrowed down to molasse for three structures and to loess, moraine or mass chalk sites for one. The isotopic ratio thus points to growing sites more in the surrounding of the concerned archaeological sites and a more distant Black Forest source can be ruled out. Local evidence of Abies was additionally supported by palynological data from four archaeological sites and by anthracological data from a funeral context near the Heuneburg.